Insight into the purification of algael water by a novel flocculant with enhanced branched nanochitosan structure. (1st April 2023) - Du, Bin; Tang, Qian; Chen, Wei; Rong, Xiang; Zhang, Ke; Ma, Dandan; Wei, Zhaolan; Chen, Wei
Abstract: For improving inadequate nanostructural stability and promote algal removal efficiency, a novel nanochitosan-grafted flocculant (PAD-g-MNC) with an enhanced branched nanostructure and high molecular weight (MW) was fabricated via maleic anhydride acylation polymerization. Characterization results verified the successful synthesis of the flocculant and the formation of an irregular particle nanostructure. PAD-g-MNC exhibited superior algal and extracellular organic matter (EOM) removal and obtained the turbidity and chlorophyll-a removal rates of 93.46%–95.39% and 95.10%–97.31%, respectively, at the dosage of 4–5 mg L −1 . The growth rate, strength factor, and recovery factor of algal flocs flocculated by PAD-g-MNC were 90.36, 0.63, and 0.27 (100 rpm), respectively, and were higher than other flocculants prepared through conventional methods. Results indicated that the high intrinsic viscosity and stability branched nanostructure promoted the formation of stable flocs and regeneration ability of flocs. MW distribution and three-dimensional fluorescence analyses revealed that the special structure of PAD-g-MNC was beneficial to the removal of tryptophan-like proteins in EOM. Strong adsorption–adhesion and bridging–netting effects of the nanostructure chain were the dominated mechanisms in the improvement of flocculation efficiency. This study provided theoretical and experimental guidance for the design of flocculants with superior performance and efficient algal water purification performance. Graphical abstract: Image 1 Highlights: Flocculant with reinforced nanostructure and intrinsic viscosity was fabricated. Acylation grafting enhanced nanostructure stability and polymerization efficiency. PAD-g-MNC obtained 95.10%–97.31% Chl-a removal. PAD-g-MNC was more inclined to remove tryptophan-like proteins in EOM flocculation. Adsorption-adhesion and bridging-netting role improved flocculation efficiency.